2017
DOI: 10.1002/ijgo.12355
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Randomized controlled trial of the effect of endometrial injury on implantation and clinical pregnancy rates during the first ICSI cycle

Abstract: Endometrial injury in the cycle preceding the stimulation cycle improved implantation and pregnancy rates during ICSI. CLINICALTRIALS.GOV: NCT02660125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(100 citation statements)
references
References 29 publications
1
98
1
Order By: Relevance
“…The risk of bias of the included RCTs is described in Table II. For seven RCTs, the risk of selection bias was unclear because the method of allocation was not clearly described (Karimzadeh et al , 2009; Baum et al , 2012; Inal et al , 2012; Singh et al , 2015; Mahran et al , 2016; Liu et al , 2017; Maged et al , 2018). Random sequence generation was interpreted to be at a low risk of selection bias because this was performed by computer-generated sequence (Narvekar et al , 2010; Safdarian et al , 2011; Inal et al , 2012; Nastri et al , 2013; Yeung et al , 2014; Gibreel et al , 2015; Singh et al , 2015; Tk et al , 2017; Maged et al , 2018), a table of random numbers (Baum et al , 2012; Liu et al , 2017), sealed envelopes (Mahran et al , 2016) or a bag of papers with equal amounts of intervention and control groups (Karimzadeh et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias of the included RCTs is described in Table II. For seven RCTs, the risk of selection bias was unclear because the method of allocation was not clearly described (Karimzadeh et al , 2009; Baum et al , 2012; Inal et al , 2012; Singh et al , 2015; Mahran et al , 2016; Liu et al , 2017; Maged et al , 2018). Random sequence generation was interpreted to be at a low risk of selection bias because this was performed by computer-generated sequence (Narvekar et al , 2010; Safdarian et al , 2011; Inal et al , 2012; Nastri et al , 2013; Yeung et al , 2014; Gibreel et al , 2015; Singh et al , 2015; Tk et al , 2017; Maged et al , 2018), a table of random numbers (Baum et al , 2012; Liu et al , 2017), sealed envelopes (Mahran et al , 2016) or a bag of papers with equal amounts of intervention and control groups (Karimzadeh et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Since the publication of the abovementioned reviews, multiple RCTs on endometrial injury prior to ART have been carried out. While the first trials mainly focused on patients with RIF, more recent studies have shifted their focus to also include patients in earlier stages of IVF/ICSI treatment (Mahran et al , 2016; Liu et al , 2017; Tk et al , 2017; Maged et al , 2018). The increase in number of published studies not only calls for an updated review of the existing body of evidence, but also has created the possibility to subgroup patients according to the number of failed IVF/ICSI cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Poor ovarian response was defined in accordance with the Bologna criteria as a minimum of two of the following factors: maternal age of 40 years or older or any other risk factor for poor response; a previous poor response to a conventional stimulation protocol (i.e., cancelled cycle or retrieval of three follicles or less); or an abnormal ovarian reserve test result (antral follicle count, <5-7; or anti-Müllerian hormone, ≤0.5-1.1 ng/mL). 17 The exclusion criteria were any factors that might affect repro- Serum β-hCG levels were assessed 14 days after embryo transfer.…”
Section: Methodsmentioning
confidence: 99%
“…Further exploration of this phenomenon in a larger group of patients, indeed showed for the fi rst time, that repeated endometrial biopsy substantially increased the IVF outcome in RIF patients [5]. This favorable effect of endometrial biopsy on IVF outcome, was later demonstrated by other clinical centers, most of which selected RIF patients undergoing IVF for their studies [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 86%